Depicting #fatherhood involvement on Instagram: Caregiving, affection, and stimulation (Communication & Society, 2022)
This article aims to analyze how fatherhood is performed on Instagram by examining the domains of involvement. Parental roles and behaviors have changed in the last years and are currently a relevant social and scientific topic. The way that fatherhood is performed is also a frequent subject on social media, spreading the ideal of a new fatherhood and portraying the father as committed to childcare duties. The hashtag “fatherhood” was used to identify posts on Instagram representing father involvement. A final sample of 121 posts was identified. Results depicted three main domains in fatherhood’s online representations of involvement: (1) child caregiving; (2) fathers as a source of the child’s affection; and (3) fathers involved in play, committed to the child’s interests and offering new opportunities of stimulation. The display of fatherhood as a role requiring dedication and effort also emerged, but to a lesser extent. Nevertheless, only positive emotions were shared, depicting pleasure in the performed role, and communicating an ideal and self-enhancing profile. Moreover, posts seemed to disseminate an ideal of fatherhood rather than raise questions or discuss the challenges related to it. Findings uncover how media social representations of fatherhood are still an unfinished process, failing to capture diversity and challenges in contemporary families.